If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + 4)(2x + 5) = 0 Reorder the terms: x(4 + x)(2x + 5) = 0 Reorder the terms: x(4 + x)(5 + 2x) = 0 Multiply (4 + x) * (5 + 2x) x(4(5 + 2x) + x(5 + 2x)) = 0 x((5 * 4 + 2x * 4) + x(5 + 2x)) = 0 x((20 + 8x) + x(5 + 2x)) = 0 x(20 + 8x + (5 * x + 2x * x)) = 0 x(20 + 8x + (5x + 2x2)) = 0 Combine like terms: 8x + 5x = 13x x(20 + 13x + 2x2) = 0 (20 * x + 13x * x + 2x2 * x) = 0 (20x + 13x2 + 2x3) = 0 Solving 20x + 13x2 + 2x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), 'x'. x(20 + 13x + 2x2) = 0 Factor a trinomial. x((4 + x)(5 + 2x)) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(4 + x)' equal to zero and attempt to solve: Simplifying 4 + x = 0 Solving 4 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + x = 0 + -4 x = 0 + -4 Combine like terms: 0 + -4 = -4 x = -4 Simplifying x = -4Subproblem 3
Set the factor '(5 + 2x)' equal to zero and attempt to solve: Simplifying 5 + 2x = 0 Solving 5 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 2x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 2x = 0 + -5 2x = 0 + -5 Combine like terms: 0 + -5 = -5 2x = -5 Divide each side by '2'. x = -2.5 Simplifying x = -2.5Solution
x = {0, -4, -2.5}
| 7x+20=72 | | 4(2x-5)=5+4 | | a=5(x+8) | | xx+2x+7=7 | | A-40=5x | | 5X*3+3X=13 | | a=5x+40 | | 1.7+5(2.1x+0.4)=2 | | 6x+4y=95 | | 7x+20=56 | | 8=x+8.4-1.2x | | 8y+13= | | 8(y-3)-3=56 | | 28y+5=49 | | 28y+5=27 | | 2x+167=11x-13 | | 7m-11=59 | | 9h+6=87 | | 7m+3=59 | | sin(2x+5)=sin(x-1) | | x^3-6x^2+20x=0 | | 2x^3-6x^2+20x=0 | | x+2.5z=18 | | 27x+11y+6z=1200 | | ln(x+7)=2 | | (60-d)(40-2d)=0 | | (60-d)(40-2d)=1312.5 | | 2a+4b+8c=200 | | x^3-2x^2-7x+6=0 | | 24(x+4)=24 | | 46(x-2)=18 | | 83(n+4)=7 |